Laser-derived porous carbon as a metal-free electrocatalyst for oxygen evolution reaction. (October 2022) - Devi, Mamta; Madan, Chetna; Halder, Aditi; Sharma, Swati
Abstract: We introduce a metal-free, high-surface-area N-containing carbon material prepared via single-step laser-induced carbonization of polyimide films as an electrocatalyst for oxygen evolution reaction (OER), which obviates the need for a loading substrate. Our inexpensive and scalable one-step fabrication process yields porous carbon films with a high atomic ratio of pyridinic and pyrrolic N functional groups. The material is activated by inducing additional oxygen-rich functional groups, resulting in more electrochemically active sites and less charge transfer resistance for superior electrocatalytic performance. The activated laser-carbon exhibits an excellent catalytic activity towards OER with an overpotential of 470 mV at a current density of 10 mA cm −2, which is much lower compared to other metal-free electrocatalysts. This multifunctional carbon material has an immense potential for the fabrication of lightweight water electrolyzers as well as in the designing of electrode for flexible solid-state metal-air batteries. Graphical abstract: Image, graphical abstract